Innovation in the Transport of Cytotoxic Drugs by a Pneumatic Transport System - Baillie Constance; Desplanques Marion; Delbey Stéphanie; Sakji Ilyes; Feutry Frédéric (De Gruyter, 2017)
Many chemotherapeutic compounding units are confronted with the problem of product delivery to different care wards. We think that transport by a pharmacy agent does not permit appropriate traceability (wrong care service delivery), control of storage temperature and management of urgency. We have developed a delivery system based on the association of a pneumatic transport system (PTS) and monitored buffer storage area. Thus, after pharmaceutical inspection, chemotherapies are placed in specific and hermetic carriers in the PTS but not directly delivered to care units. In the monitored buffer storage, a robotic arm organizes chemotherapies and waits for the nurse call just before administration. This system permits a real traceability for each stage of the chemotherapy circuit and so, we are now able to certify that chemotherapeutics have been maintained at the correct temperature through continual monitoring. It's an important prerequisite in standardization and reassignment. Finally, an important issue linked to the use of PTS is the risk of damaging the chemotherapeutics. Data obtained from literature and manufacturers for antibodies highlight the low risk to use a PTS.